ANALISIS PENGUKURAN KINERJA PERUSAHAAN DENGAN MENGGUNAKAN METODE BALANCED SCORECARD PADA PERUSAHAAN DAERAH AIR MINUM SURAKARTA TAHUN 2015 – 2016 - Setyaningsih Sri Utami, Vina Pratiwi, Edi Wibowo & (Universitas Slamet Riyadi, 2018)
The purpose of this study is to measure the performance of PDAM Surakarta using Balanced Scorecard method. This research was conducted taking data for 2 years, from 2015 and 2016 from PDAM annual report and annual financial report of PDAM. The type of data used is qualitative and quantitative data. Sources of data used are secondary data. Technique of collecting data with documentation, literature study and observation. Furthermore, the researcher compared the theories that become the basis of the research by using four perspectives: financial perspective, customer perspective, internal business perspective, learning and growth perspective, after measured by those four perspectives, PDAM will get the level of performance measure. From the results of the study shows that financial perspective has good results, Customer's perspective has poor results, Internal business perspective has good result, Learning perspective and growth have bad result. Surakarta PDAM performance measured by balanced scorecard method has good result, customer perspective and learning and growth perspective need to be improved its performance.Keywords: performance measurement, financial perspective, customer perspective, internal business perspective, learning and growth perspective, PDAM Surakarta